Which of the following equations has a sum of -7.

4x-23=5
5x+11=-24
-3x-8=-29
-x+3=-4

3 answers

To find the equation with a sum of -7, we can rearrange each equation so that it is in the form of 'sum = -7'.

1) 4x - 23 + 5 = -7
Simplifying, we have:
4x - 18 = -7
4x = 11
x = 11/4
This equation does not have a sum of -7.

2) 5x + 11 - 24 = -7
Simplifying, we have:
5x - 13 = -7
5x = 6
x = 6/5
This equation does not have a sum of -7.

3) -3x - 8 + 29 = -7
Simplifying, we have:
-3x + 21 = -7
-3x = -28
x = 28/3
This equation does not have a sum of -7.

4) -x + 3 + 4 = -7
Simplifying, we have:
-x + 7 = -7
-x = -14
x = 14
This equation does not have a sum of -7.

Therefore, none of the given equations has a sum of -7.
Here are the equations again
A. 4x-23=5
B. -3x-8=-29
C. -x+3=-4
D. 5x+11=-24
To find the equation with a sum of -7, we can rearrange each equation so that it is in the form of 'sum = -7'.

A. 4x - 23 = 5
Adding 23 to both sides:
4x = 28
Dividing both sides by 4:
x = 7
This equation does not have a sum of -7.

B. -3x - 8 = -29
Adding 8 to both sides:
-3x = -21
Dividing both sides by -3:
x = 7
This equation does not have a sum of -7.

C. -x + 3 = -4
Adding x to both sides:
3 = -4 + x
Adding 4 to both sides:
7 = x
This equation does have a sum of -7.

D. 5x + 11 = -24
Subtracting 11 from both sides:
5x = -35
Dividing both sides by 5:
x = -7
This equation does not have a sum of -7.

Therefore, the equation with a sum of -7 is C. -x + 3 = -4.